Identifikasi Morfologi Beberapa Spesies Jamur Fusarium - Ade Mahendra Sutejo; Achmadi Priyatmojo; Arif Wibowo (Universitas Gadjah Mada, 2008)
The research was conducted to study the morphological difference based on macroscopic and microscopic appearance of several Fusarium spp. Fusarium spp. isolates were propagated onto Potato Dextrose Agar (PDA) by using single-spore method. All isolates were observed macroscopically and microscopically to determine colony appearance, colony growth diameter and formation of macroconidia, microconidia and conidiophores. The results showed that colony appearance of all isolates was similar. Therefore they could not clearly be differentiated by one to another. On the other hand, microscopic observation showed that there was different conidiophore morphology of F. oxysporum and other Fusarium spp. Microscopic morphology among F. oxysporum isolates were difficult to differentiate. Microconidia were produced in false-head which was the characteristic feature of most F. oxysporum. In conclusion, microscopic morphology observation could only be able to differentiate Fusarium spp. isolates at species level, but not to formae speciales.